Lightweight magnetic carbon composite loss type PMI foam with wave-absorbing function and preparation method thereof
Through the uniform dispersion technology of lightweight carbon-covered magnetic metal absorbers, the lack of wave absorption function and traditional carbon material settlement problems in aircraft stealth applications is solved, achieving high-performance wave absorption and mechanical performance improvement.
Patent Information
- Application Number
- CN202411369958.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-14
AI Technical Summary
The existing PMI foam lacks radar wave absorption function in aircraft stealth applications. Traditional carbon materials have settlement problems during the preparation process, which affects the wave absorption effect and mechanical properties.
Using light carbon-covered magnetic metal absorber, the co-carbonization technology of self-decomposition templates and metal organic complexes can achieve uniform dispersion of carbon-covered magnetic metal absorber, combined with mechanical stirring and shear homogenization treatment to ensure the wave absorber Compatibility and uniform dispersion in PMI foam systems.
It achieves uniform foaming and excellent wave absorption performance of PMI foam, improves the mechanical properties of the product, and meets the potential application needs in the military field.
Smart Images

Figure CN119307060A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam materials, in particular to a lightweight magnetic-carbon composite lossy PMI foam with wave absorbing function and a preparation method thereof. Background Art
[0002] Foam with wave-absorbing function is an important functional foam material in the current aviation, UAV, anti-radar detection and other industries, and is of great significance to improving the penetration and survivability of weapons and equipment. Polymethacrylimide (PMI) foam is a structural rigid foam with an imide ring structure, closed cells, and uniform cross-linking generated by cycloisomerization. It has good mechanical properties (high strength and high modulus), heat deformation temperature, chemical stability, and light weight, and has attracted widespread attention in the field of high-performance structural composite materials.
[0003] However, most of the PMI foams currently sold on the market are high-strength wave-transmitting materials without any frequency band radar wave absorption function, which cannot meet the application requirements in special fields such as aircraft stealth, and seriously restrict the development of my country's national defense industry. In order to make PMI foam have wave-absorbing properties, wave-absorbing agents need to be added in the process of preparing PMI foam. In recent years, domestic and foreign researchers have explored various methods, such as mixing wave-absorbing agent powders such as carbon materials with pre-polymerized and broken PMI foams and foaming them to obtain PMI composite foams. However, the conductive fillers in the prepared PMI composite foams are in a discontinuous state, the foaming is uneven, the quality of the finished product is poor, and good conductivity and wave-absorbing effects are not achieved. At the same time, the mechanical properties of the original PMI foam are affected. In-situ polymerization of absorbents has gradually become the main way to prepare wave-absorbing PMI composite foams. Among them, carbon materials have the characteristics of light weight, stability, and adjustable dielectric properties, and are the primary filler choice for preparing PMI wave-absorbing foams. However, the polymerization and foaming time of PMI is long, and the compatibility requirements between the filler and the system are extremely high. Traditional carbon materials or magnetic carbon composite materials have the disadvantages of large structural size, high density, and limited intrinsic conductivity, which can easily cause the system to settle. Therefore, it is necessary to carry out the structural design and preparation of carbon-based materials in a targeted manner. For example, the magnetic loss capacity of the material can be improved by introducing magnetic materials, but the problem of lightweight materials needs to be solved. In addition, if anti-precipitation technology or uniform dispersion technology is not used in the preparation method, the filler will settle seriously during the polymerization process, and the absorber will find it difficult to exert its maximum effect. The foam has poor conductivity and is difficult to meet certain wave absorption requirements, and even seriously damages the original mechanical properties of the PMI foam. Therefore, it is urgent to develop new lightweight carbon-based composite absorbers in a targeted manner, such as lightweight carbon nanotubes with complete structures, graphene, lightweight magnetic / carbon composite materials, etc., to promote the practical application of wave-absorbing functional PMI foam in weapons and equipment. Summary of the invention
[0004] The purpose of the present invention is to provide a lightweight magnetic-carbon composite lossy absorbing functional PMI foam. Through the structural preparation of lightweight carbon-coated magnetic metal absorbers and the compound design of carbon materials, the sedimentation problem in the PMI polymerization and foaming process is solved, and the compatibility and dispersion problem of lightweight carbon-coated magnetic metal absorbers in the PMI foam system is solved, so as to realize the controllable preparation of PMI foam materials with integrated load-bearing structure function and stealth function, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A lightweight magnetic-carbon composite lossy PMI foam with absorbing function, comprising the use of self-decomposing templates and metal-organic ligand co-carbonization technology to achieve controllable preparation of lightweight carbon-coated magnetic metal absorbers, including carbon-coated ferromagnetic absorbers, carbon-coated cobalt magnetic absorbers and carbon-coated nickel magnetic absorbers, etc. The lightweight carbon-coated magnetic metal absorbers are fully mixed and uniformly dispersed in a PMI precursor solution after mechanical stirring pre-treatment and shearing homogenization post-treatment, and then filled into a specific mold for polymerization, and then foamed to obtain the PMI foam with absorbing function.
[0007] Another object of the present invention is to provide a method for preparing a lightweight magnetic-carbon composite lossy PMI foam with microwave absorption function, which specifically comprises the following steps:
[0008] Step 1: Pour urea or melamine or both into a ceramic crucible with a lid, then place the ceramic crucible in a muffle furnace for program heat treatment, and finally stop heating and allow it to cool naturally to room temperature. The resulting light yellow substance is carbon nitride, which is ground and crushed for later use;
[0009] Step 2: Weigh a certain mass of prepared carbon nitride powder and an organic metal complex (the organic metal complex is one or more of cobalt (II) acetylacetonate, nickel acetylacetonate, ferrous acetylacetonate, ferrous gluconate, cobalt gluconate, nickel gluconate, ferrocene, nickelocene, cobaltocene, etc.), and mix the two evenly by a high-speed ball mill;
[0010] Step 3: Pour the mixture into a closed reactor and perform high-temperature carbonization treatment, and naturally cool to room temperature after carbonization;
[0011] Step 4: Collect the black powder in the reaction kettle, which is the desired lightweight carbon-coated magnetic metal absorbent;
[0012] Step 5: Weigh the following materials by mass to prepare the PMI precursor solution:
[0013] Methacrylic acid 60%-45%, methacrylonitrile 40%-55%, acrylamide 0.5%-0.8%, initiator 0.15-0.28%, preferably a combination of dibenzoyl peroxide, dodecyl peroxide, peroxydicarbonate and tert-butyl perbenzoate, the ratio of the four is (0.5-2.5):(1.5-4):(2.5-5.5):(2-4), blowing agent 5%-15%, preferably a combination of formamide, tert-butyl alcohol and isopropanol, the mass ratio of the three is 6:3:2.5, heat-resistant agent is N-phenylmaleimide, the mass ratio is 0.5-3%, and heat stabilizer zinc stearate is 1.5%-3%.
[0014] Step 6: Weigh the light carbon-coated magnetic metal absorber and the PMI precursor solution in a ratio of 1:1.5% to 1:15% respectively;
[0015] Step 7: Add the lightweight carbon-coated magnetic metal absorbent to the PMI precursor solution and mechanically stir for 1 h to 5 h;
[0016] Step 8: The pre-mixed absorbing slurry is uniformly sheared and homogenized again for 1 to 5 times by a shearing and homogenizing device;
[0017] Step nine: Fill the uniformly dispersed absorbing slurry into a specific mold and polymerize it in a constant temperature water bath at 36°C to 50°C for 10 to 12 days;
[0018] Step 10: After demolding, the polymerized board is heat treated at 70°C to 90°C for 18 hours and demolded; at 140°C to 220°C, foaming is performed for 6 to 12 hours, and the foamed product is appropriately peeled or trimmed to obtain a lightweight magnetic-carbon composite lossy absorbing PMI foam board.
[0019] As a further solution of the present invention: the heat treatment in step 1 specifically includes: first heating from room temperature to 450-600°C at a heating rate of 2-4°C / min, and then maintaining the reaction at a set high temperature condition of 450-600°C for 2-6h.
[0020] As a further solution of the present invention: the high temperature calcination in the step three specifically includes: performing programmed temperature calcination in an argon atmosphere, heating to 700-900°C at a heating rate of 5-10°C / min, maintaining the temperature under the set target temperature conditions for 1-4 hours and then stopping the heating, and the corresponding light carbon-coated magnetic metal absorbent can be obtained.
[0021] As a further solution of the present invention: the lightweight magnetic carbon-based absorbent in step 4 includes one or more combinations of carbon-coated ferromagnetic absorbent, carbon-coated cobalt magnetic absorbent and carbon-coated nickel magnetic absorbent.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In order to overcome the problems of long polymerization time, sedimentation of absorbent, uneven foaming, and poor absorbing effect in the process of preparing absorbing PMI foam by in-situ polymerization, this invention provides a high-performance lightweight carbon-coated magnetic metal absorbent, and realizes uniform dispersion of lightweight carbon-coated magnetic metal absorbent in PMI foam through shear dispersion treatment process. Different types of lightweight carbon-coated magnetic metal absorbents are selected and added to the precursor solution of PMI foam, and the lightweight carbon-coated magnetic metal absorbents are fully mixed and evenly dispersed in the PMI precursor solution through mechanical stirring pre-treatment and shear homogenization post-treatment, and then filled into a specific mold for polymerization, and then foamed to obtain PMI foam with uniform foaming, good dispersion of absorbent, and dual functions of absorbing and carrying. The process avoids the effective sedimentation of the absorbent, and at the same time makes the foamed product uniform, which greatly improves the mechanical properties of the PMI foam product with absorbing function. The foam material has great potential application value in the military field. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 : Scanning image of PMI foam with microwave absorption function of lightweight carbon-coated cobalt magnetic absorber prepared using cobalt (II) acetylacetonate;
[0025] Figure 2 :Microwave-absorbing PMI foam with lightweight carbon-coated cobalt magnetic absorber prepared using cobalt(II) acetylacetonate
[0026] Figure 3 : PMI foam with microwave absorption function prepared by using cobalt (II) acetylacetonate as lightweight carbon-coated cobalt magnetic absorber;
[0027] Figure 4 : Scanning image of PMI foam with microwave absorption function of lightweight carbon-coated nickel magnetic absorber prepared using nickel acetylacetonate;
[0028] Figure 5 : Wave absorption performance diagram of PMI foam with wave absorption function of lightweight carbon-coated nickel magnetic absorber prepared using nickel acetylacetonate;
[0029] Figure 6 : Scanning image of microwave-absorbing PMI foam with lightweight carbon-coated ferromagnetic absorber prepared using ferrocene;
[0030] Figure 7 : Wave absorption performance diagram of PMI foam with wave absorption function of lightweight carbon-coated ferromagnetic absorber prepared using ferrocene;
[0031] Figure 8 : Scanning image of microwave-absorbing PMI foam with lightweight carbon-coated ferromagnetic absorber prepared using cobalt gluconate;
[0032] Fig. 9 : Wave absorption performance diagram of PMI foam with wave absorption function of lightweight carbon-coated ferromagnetic absorber prepared using cobalt gluconate;
[0033] Fig.10 : Scanning image of PMI foam with microwave absorption function using lightweight carbon-coated nickel magnetic absorber prepared by nickelocene;
[0034] Fig.11 : Wave absorption performance diagram of PMI foam with wave absorption function of lightweight carbon-coated nickel magnetic absorber prepared using nickelocene;
[0035] Fig.12 : Scanning image of PMI foam with microwave absorption function of lightweight carbon-coated ferromagnetic absorber prepared using ferrous gluconate;
[0036] Fig.13 : Wave absorption performance diagram of PMI foam with wave absorption function of lightweight carbon-coated ferromagnetic absorber prepared using ferrous gluconate; DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] A light magnetic carbon composite lossy PMI foam with microwave absorption function, comprising a light carbon-coated magnetic metal absorber, wherein the light carbon-coated magnetic metal absorber is fully mixed and uniformly dispersed in a PMI precursor solution after mechanical stirring pre-treatment and shearing homogenization post-treatment, and then filled into a specific mold for polymerization, and then foamed to obtain a microwave absorption PMI foam, specifically comprising the following steps:
[0039] Step 1: Pour urea or melamine or both into a ceramic crucible with a lid, then place the ceramic crucible in a muffle furnace for program heat treatment, and finally stop heating and allow it to cool naturally to room temperature. The resulting light yellow substance is carbon nitride, which is ground and crushed for later use;
[0040] Step 2: Weigh a certain mass of prepared carbon nitride powder and an organic metal complex (the organic metal complex is one or more of cobalt (II) acetylacetonate, nickel acetylacetonate, ferrous acetylacetonate, ferrous gluconate, cobalt gluconate, nickel gluconate, ferrocene, nickelocene, cobaltocene, etc.), and mix the two evenly by a high-speed ball mill;
[0041] Step 3: Pour the mixture into a closed reactor and perform high-temperature carbonization treatment, and naturally cool to room temperature after carbonization;
[0042] Step 4: Collect the black powder in the reaction kettle, which is the desired lightweight carbon-coated magnetic metal absorbent;
[0043] Step 5: Weigh the following materials by mass to prepare the PMI precursor solution:
[0044] Methacrylic acid 60%-45%, methacrylonitrile 40%-55%, acrylamide 0.5%-0.8%, initiator 0.15-0.28%, preferably a combination of dibenzoyl peroxide, dodecyl peroxide, peroxydicarbonate and tert-butyl perbenzoate, the ratio of the four is (0.5-2.5):(1.5-4):(2.5-5.5):(2-4), blowing agent 5%-15%, preferably a combination of formamide, tert-butyl alcohol and isopropanol, the mass ratio of the three is 6:3:2.5, heat-resistant agent is N-phenylmaleimide, the mass ratio is 0.5-3%, and heat stabilizer zinc stearate is 1.5%-3%.
[0045] Step 6: Weigh the light carbon-coated magnetic metal absorber and the PMI precursor solution in a ratio of 1:1.5% to 1:15% respectively;
[0046] Step 7: Add the lightweight carbon-coated magnetic metal absorbent to the PMI precursor solution and mechanically stir for 1 h to 5 h;
[0047] Step 8: The pre-mixed absorbing slurry is uniformly sheared and homogenized again for 1 to 5 times by a shearing and homogenizing device;
[0048] Step nine: Fill the uniformly dispersed absorbing slurry into a specific mold and polymerize it in a constant temperature water bath at 36°C to 50°C for 10 to 20 days;
[0049] Step 10: After demolding, the polymerized board is heat treated at 70°C to 90°C for 12 hours and demolded; at 140°C to 220°C, it is foamed for 6 to 12 hours, and the foamed product is appropriately peeled or trimmed to obtain a lightweight magnetic-carbon composite lossy absorbing PMI foam board.
[0050] Electromagnetic wave absorption performance test steps: Test according to the bow test method in the existing conventional test method GJB2038A radar absorbing material reflectivity test method.
[0051] Step 1: Cutting: Cut the lightweight magnetic carbon composite lossy absorbing PMI foam obtained in the above step into 180mm×180mm square plates with a specific tool for later use. Multiple square plates of the same sample need to be prepared for testing to minimize experimental errors.
[0052] Step 2: Test: The instrument used for the test is a vector network analyzer. The bow method is used to test in the frequency range of 1-18GHz and draw the wave absorption performance curve.
[0053] Embodiment 1:
[0054] The present invention provides a method for preparing a lightweight magnetic carbon composite lossy PMI foam with microwave absorption function, for example, using cobalt (II) acetylacetonate to prepare a lightweight carbon-coated cobalt magnetic absorber, and then using the same to prepare a microwave absorption PMI foam, the preparation steps are as follows:
[0055] Pour urea into a ceramic crucible with a lid, and then place the ceramic crucible in a muffle furnace for program heat treatment: first heat from room temperature to 550°C at a heating rate of 2.3°C / min, then keep it at a high temperature of 550°C for 4h, and finally stop heating and let it cool naturally to room temperature. The light yellow substance obtained is carbon nitride, which is ground and crushed for standby use. Weigh 500g of the prepared carbon nitride and 125g of acetylacetonate cobalt (II), and mix the two evenly through a pulverizer. Pour the mixture into a closed reactor for high-temperature calcination treatment, program temperature calcination under an argon atmosphere, and heat to 850°C at a heating rate of 5°C / min. After the reaction is maintained at 850°C for two hours, stop heating and cool naturally to room temperature. Collect the black powder in the reactor, which is the required lightweight carbon-coated cobalt magnetic absorbent. Weigh a certain mass of PMI precursor solution and lightweight carbon-coated cobalt magnetic absorbent in a certain proportion, where the mass fraction of the absorbent accounts for 8%. A light carbon-coated cobalt magnetic absorber is added to the PMI precursor solution, mechanically stirred and mixed for 3 hours, and then dispersed three times again through a shear homogenization device. The evenly dispersed absorbing slurry is filled into a specific mold, polymerized in a constant temperature water bath at 38°C for 7 days, then heated to 42°C and kept warm for 5 days, and after the resin plate is mirror-finished, heated to 48°C and kept warm for 6 days. Heat treatment is carried out at 85°C for 18 hours and demolding; the polymerization product is preheated at 145°C for 4 hours, and after the resin plate expands, the temperature is raised to 175°C and kept warm for 1 hour, and then heated to 215°C for foaming for 3 hours. The foamed product is appropriately peeled or trimmed to obtain a PMI foam with absorbing function.
[0056] like Figure 1 and Figure 2As shown, the large-scale wave-absorbing PMI foam prepared by using light carbon-coated cobalt magnetic absorber exhibits a relatively uniform closed-cell structure. The density of the PMI foam prepared in this example is 76.15 kg / m 3 , compression strength 0.97MPa, compression modulus 72.94MPa, tensile strength 1.29MPa, tensile modulus 92.80MPa, shear strength 0.82MPa, shear modulus 32.61MPa. Due to the porous foam structure and lightweight magnetic carbon composite lossy absorber, the foam has excellent wave absorption performance. Figure 3 As shown, the strongest reflection loss (RL) reaches -32.08dB, and the effective absorption bandwidth (EAB, RL≤-10dB) can reach 11.86GHz, covering bands including L, C, X, and Ku.
[0057] Embodiment 2:
[0058] The present invention provides a method for preparing a lightweight magnetic carbon composite lossy PMI foam with microwave absorption function. For example, nickel acetylacetonate is used to prepare a lightweight carbon-coated nickel magnetic absorber, and then the same is used to prepare a microwave absorption PMI foam. The preparation steps are as follows:
[0059] Pour urea into a ceramic crucible with a lid, and then place the ceramic crucible in a muffle furnace for program heat treatment: first heat from room temperature to 550°C at a heating rate of 2.3°C / min, then keep it at a high temperature of 550°C for 4h, and finally stop heating and let it cool naturally to room temperature. The light yellow substance obtained is carbon nitride, which is ground and crushed for standby use. Weigh 500g of the prepared carbon nitride and 125g of nickel acetylacetonate, and mix the two evenly through a pulverizer. Pour the mixture into a closed reactor for high-temperature calcination treatment, program temperature calcination under an argon atmosphere, and heat to 800°C at a heating rate of 5°C / min. After the reaction is maintained at 800°C for 2h, stop heating and cool naturally to room temperature. Collect the black powder in the reactor, which is the required lightweight carbon-coated nickel magnetic absorbent. Weigh a certain mass of PMI precursor solution and lightweight carbon-coated nickel magnetic absorbent in a certain proportion, where the mass percentage of the absorbent is 8%. Add the lightweight carbon-coated nickel magnetic absorber to the PMI precursor solution, stir mechanically for 3 hours, and then disperse it again through the shear homogenization equipment for 3 times. Fill the evenly dispersed absorbing slurry into a specific mold, polymerize it in a constant temperature water bath at 38°C for 7 days, then heat it to 42°C and keep it warm for 5 days, and heat it to 48°C and keep it warm for 6 days after the resin plate is mirrored. Heat treat it at 85°C for 18 hours and demould it; preheat the polymerized product at 145°C for 4 hours, heat it to 175°C and keep it warm for 1 hour after the resin plate expands, and then heat it to 215°C for foaming for 3 hours, peel or trim the foamed product appropriately, and you will get the absorbing PMI foam.
[0060] like Figure 4 As shown, the PMI foam with microwave absorption function prepared by using light carbon-coated nickel magnetic absorber has a relatively uniform closed-cell structure. The density of the PMI foam prepared in this example is 78.91 kg / m 3 , compression strength 1.55MPa, compression modulus 80.26MPa, tensile strength 1.96MPa, tensile modulus 107.18MPa, shear strength 1.09MPa, shear modulus 49.14MPa. Due to the porous foam structure and lightweight magnetic carbon composite lossy absorber, the foam has excellent wave absorption performance. Figure 5 As shown, the strongest reflection loss (RL) reaches -23.54dB, and the effective absorption bandwidth (EAB, RL≤-10dB) can reach 12.80GHz, covering bands including S, C, X, and Ku.
[0061] Embodiment 3:
[0062] The present invention provides a method for preparing a lightweight magnetic carbon composite lossy PMI foam with microwave absorption function. For example, ferrocene is used to prepare a lightweight carbon-coated ferromagnetic absorber, and then the light carbon-coated ferromagnetic absorber is used to prepare a microwave absorption PMI foam. The preparation steps are as follows:
[0063] Pour melamine into a ceramic crucible with a lid, and then place the ceramic crucible in a muffle furnace for program heat treatment: first heat from room temperature to 520°C at a heating rate of 3.0°C / min, then keep it at a high temperature of 520°C for 4h, and finally stop heating and let it cool naturally to room temperature. The light yellow substance obtained is carbon nitride, which is ground and crushed for standby use. Weigh 500g of prepared carbon nitride and 125g of ferrocene, and mix the two evenly through a pulverizer. Pour the mixture into a closed reactor for high-temperature calcination treatment, program temperature calcination under an argon atmosphere, and heat to 800°C at a heating rate of 5°C / min. After the reaction is maintained at 800°C for 2h, stop heating and cool naturally to room temperature. Collect the black powder in the reactor, which is the required light carbon-coated ferromagnetic absorbent. Weigh a certain mass of PMI precursor solution and light carbon-coated ferromagnetic absorbent in a certain proportion, where the mass ratio of the absorbent is 8%. Add the lightweight carbon-coated ferromagnetic absorber to the PMI precursor solution, stir mechanically for 3 hours, and then disperse it again through the shear homogenization equipment for 3 times. Fill the evenly dispersed absorbing slurry into a specific mold, polymerize it in a constant temperature water bath at 38°C for 7 days, then heat it to 42°C and keep it warm for 5 days, and heat it to 48°C and keep it warm for 6 days after the resin plate is mirrored. Heat treat it at 85°C for 18 hours and demould it; preheat the polymerized product at 145°C for 4 hours, heat it to 175°C and keep it warm for 1 hour after the resin plate expands, and then heat it to 215°C for foaming for 3 hours, peel or trim the foamed product appropriately, and you will get the PMI foam with absorbing function.
[0064] like Figure 6 As shown, scanning electron microscopy showed that the PMI foam with microwave absorption function prepared by using light carbon coated ferromagnetic absorber showed a relatively uniform closed-cell structure inside. The density of the PMI foam prepared in this example is 77.17 kg / m 3 , compression strength 0.97MPa, compression modulus 73.46MPa, tensile strength 1.05Mpa, tensile modulus 89.05Mpa. Due to the porous foam structure and lightweight magnetic carbon composite lossy absorber, the foam has excellent wave absorption performance. Figure 7 As shown, the strongest reflection loss (RL) reaches -26.30dB, and the effective absorption bandwidth (EAB, RL≤-10dB) can reach 14.00GHz, covering bands including L, C, X, and Ku.
[0065] Embodiment 4:
[0066] The present invention provides a method for preparing a lightweight magnetic carbon composite lossy PMI foam with microwave absorption function. For example, cobalt gluconate is used to prepare a lightweight carbon-coated cobalt magnetic absorber, and then the same is used to prepare a microwave absorption PMI foam. The preparation steps are as follows:
[0067] Pour melamine into a ceramic crucible with a lid, and then place the ceramic crucible in a muffle furnace for program heat treatment: first heat from room temperature to 520°C at a heating rate of 3.0°C / min, then keep it at a high temperature of 520°C for 4h, and finally stop heating and let it cool naturally to room temperature. The light yellow substance obtained is carbon nitride, which is ground and crushed for standby use. Weigh 500g of prepared carbon nitride and 200g of cobalt gluconate, and mix the two evenly through a pulverizer. Pour the mixture into a closed reactor for high-temperature calcination treatment, program temperature calcination under an argon atmosphere, and heat to 800°C at a heating rate of 5°C / min. After the reaction is maintained at 800°C for 2h, stop heating and cool naturally to room temperature. Collect the black powder in the reactor, which is the required lightweight carbon-coated cobalt magnetic absorbent. Weigh a certain mass of PMI precursor solution and lightweight carbon-coated iron composite material in a certain proportion, wherein the mass ratio of the absorbent is 6%. Add the light carbon-coated cobalt magnetic absorber to the PMI precursor solution, stir mechanically for 3 hours, and then disperse it again through a homogenizing shearing device. Fill the evenly dispersed absorbing slurry into a specific mold, polymerize it in a constant temperature water bath at 38°C for 7 days, then heat it to 42°C and keep it for 5 days, and heat it to 48°C and keep it for 6 days after the resin plate is mirrored. Heat treat it at 85°C for 18 hours and demould it; preheat the polymerized product at 145°C for 4 hours, heat it to 175°C and keep it for 1 hour after the resin plate expands, and then heat it to 215°C for foaming for 3 hours, peel or trim the foamed product appropriately, and you will get the absorbing PMI foam.
[0068] like Figure 8 As shown, the PMI foam with microwave absorption function prepared by the light carbon-coated cobalt magnetic absorber showed a relatively uniform closed-cell structure inside by scanning electron microscopy. The density of the PMI foam prepared in this example is 77.17 kg / m 3 , compression strength 0.97MPa, compression modulus 73.46MPa, tensile strength 1.05MPa, tensile modulus 89.05MPa. Due to the porous foam structure and lightweight magnetic carbon composite lossy absorber, the foam has excellent wave absorption performance. Fig. 9 As shown, the strongest reflection loss (RL) reaches -44.97dB, and the effective absorption bandwidth (EAB, RL≤-10dB) can reach 12.83GHz, covering bands including L, S, C, X, and Ku.
[0069] Embodiment 5:
[0070] The present invention provides a method for preparing a lightweight magnetic carbon composite lossy PMI foam with microwave absorption function. For example, nickelocene is used to prepare a lightweight carbon-coated nickel magnetic absorber, and then the preparation steps of the PMI foam with microwave absorption function are as follows:
[0071] Pour melamine into a ceramic crucible with a lid, and then place the ceramic crucible in a muffle furnace for program heat treatment: first heat from room temperature to 520°C at a heating rate of 3.0°C / min, then keep it at a high temperature of 520°C for 4h, and finally stop heating and let it cool naturally to room temperature. The light yellow substance obtained is carbon nitride, which is ground and crushed for standby use. Weigh 500g of prepared carbon nitride and 200g of nickelocene, and mix the two evenly through a pulverizer. Pour the mixture into a closed reactor for high-temperature calcination treatment, program temperature calcination under an argon atmosphere, and heat to 800°C at a heating rate of 5°C / min. After the reaction is maintained at 800°C for 2h, stop heating and cool naturally to room temperature. Collect the black powder in the reactor, which is the required lightweight carbon-coated nickel magnetic absorbent. Weigh a certain mass of PMI precursor solution and lightweight carbon-coated iron composite material in a certain proportion, wherein the mass ratio of the absorbent is 6%. Lightweight carbon-coated nickel magnetic absorber was added to the PMI precursor solution, mechanically stirred and mixed for 3 hours, and then dispersed again by homogenization shearing equipment for 3 times. The evenly dispersed absorbing slurry was filled into a specific mold, polymerized in a constant temperature water bath at 38°C for 7 days, then heated to 42°C and kept warm for 5 days, and after the resin plate was mirrored, heated to 48°C and kept warm for 6 days. Heat treated at 85°C for 18 hours and demolded; the polymerized product was preheated at 145°C for 4 hours, and after the resin plate expanded, heated to 175°C and kept warm for 1 hour, and then heated to 215°C for foaming for 3 hours. The foamed product was appropriately peeled or trimmed to obtain the absorbing PMI foam.
[0072] like Fig.10As shown, the PMI foam with microwave absorption function prepared by the light carbon-coated nickel magnetic absorber showed a relatively uniform closed-cell structure inside by scanning electron microscopy. The density of the PMI foam prepared in this example is 77.78 kg / m 3 , compression strength 1.34MPa, compression modulus 81.07MPa, tensile strength 1.81MPa, tensile modulus 103.67MPa, shear strength 1.04MPa, shear modulus 43.68MPa. Due to the porous foam structure and lightweight magnetic carbon composite lossy absorber, the foam has excellent wave absorption performance. Fig.11 As shown, the strongest reflection loss (RL) reaches -19.66dB, and the effective absorption bandwidth (EAB, RL≤-10dB) can reach 13.45GHz, covering bands including L, C, X, and Ku.
[0073] Embodiment 6:
[0074] The present invention provides a method for preparing a lightweight magnetic carbon composite lossy PMI foam with microwave absorption function. For example, ferrous gluconate is used to prepare a lightweight carbon-coated ferromagnetic absorber, and then the light carbon-coated ferromagnetic absorber is used to prepare a microwave absorption PMI foam. The preparation steps are as follows:
[0075] Pour melamine into a ceramic crucible with a lid, and then place the ceramic crucible in a muffle furnace for program heat treatment: first, heat from room temperature to 520°C at a heating rate of 3.0°C / min, then keep it at a high temperature of 520°C for 4h, and finally stop heating and let it cool naturally to room temperature. The light yellow substance obtained is carbon nitride, which is ground and crushed for standby use. Weigh 500g of prepared carbon nitride and 200g of ferrous gluconate, and mix the two evenly through a pulverizer. Pour the mixture into a closed reactor for high-temperature calcination treatment, program temperature calcination under an argon atmosphere, and heat to 800°C at a heating rate of 5°C / min. After the reaction is maintained at 800°C for 2h, stop heating and cool naturally to room temperature. Collect the black powder in the reactor, which is the required light carbon-coated ferromagnetic absorbent. Weigh a certain mass of PMI precursor solution and light carbon-coated ferromagnetic absorbent in a certain proportion, where the mass ratio of the absorbent is 6%. Add the lightweight carbon-coated ferromagnetic absorber to the PMI precursor solution, stir mechanically for 3 hours, and then disperse it again through the shear homogenization equipment for 3 times. Fill the evenly dispersed absorbing slurry into a specific mold, polymerize it in a constant temperature water bath at 38°C for 7 days, then heat it to 42°C and keep it warm for 5 days, and heat it to 48°C and keep it warm for 6 days after the resin plate is mirrored. Heat treat it at 85°C for 18 hours and demould it; preheat the polymerized product at 145°C for 4 hours, heat it to 175°C and keep it warm for 1 hour after the resin plate expands, and then heat it to 215°C for foaming for 3 hours, peel or trim the foamed product appropriately, and you will get the PMI foam with absorbing function.
[0076] like Fig.12 As shown, the microwave absorbing PMI foam prepared by the light carbon-coated ferromagnetic absorber showed a relatively uniform closed-cell structure. The microwave absorbing PMI foam prepared in this example had a density of 77.78 kg / m 3 , compression strength 1.34MPa, compression modulus 81.07MPa, tensile strength 1.81MPa, tensile modulus 103.67MPa, shear strength 1.04MPa, shear modulus 43.68MPa. Due to the porous foam structure and lightweight magnetic carbon composite lossy absorber, the foam has good wave absorption performance. Fig.13 As shown, the strongest reflection loss (RL) reaches -14.11dB, and the effective absorption bandwidth (EAB, RL≤-10dB) can reach 6.01GHz, which can cover bands including L and Ku.
[0077] It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Although this specification is described in accordance with the implementation modes, not every implementation mode includes only one technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A lightweight magnetic carbon composite lossy wave absorbing functional PMI foam, characterized in that: The invention comprises a light carbon-coated magnetic metal absorber and a PMI precursor solution. The carbon-coated metal magnetic absorber is added into a precursor solution of a PMI foam. After mechanical stirring pre-treatment and shearing homogenization post-treatment, the absorber is fully mixed and evenly dispersed in the PMI precursor solution. The absorber is then filled into a specific mold for polymerization and then foamed to obtain a light magnetic-carbon composite lossy wave-absorbing PMI foam.
2. The method for preparing a lightweight magnetic-carbon composite lossy microwave-absorbing PMI foam according to claim 1, characterized in that: The specific steps include: Step 1: Pour urea or melamine or both into a ceramic crucible with a lid, then place the ceramic crucible in a muffle furnace for program heat treatment, and finally stop heating and allow it to cool naturally to room temperature. The resulting light yellow substance is carbon nitride, which is ground and crushed for later use; Step 2: Weigh a certain mass of prepared carbon nitride powder and an organic metal complex (the organic metal complex is one or more of cobalt (II) acetylacetonate, nickel acetylacetonate, ferrous acetylacetonate, ferrous gluconate, cobalt gluconate, nickel gluconate, ferrocene, nickelocene, cobaltocene, etc.), and mix the two evenly by a high-speed ball mill; Step 3: Pour the mixture into a closed reactor and perform high-temperature carbonization treatment, and naturally cool to room temperature after carbonization; Step 4: Collect the black powder in the reaction kettle, which is the desired lightweight carbon-coated magnetic metal absorbent; Step 5: Weigh the following materials by mass to prepare the PMI precursor solution: Methacrylic acid 60%-45%, methacrylonitrile 40%-55%, acrylamide 0.5%-0.8%, initiator 0.15-0.28%, preferably a combination of dibenzoyl peroxide, dodecyl peroxide, peroxydicarbonate and tert-butyl perbenzoate, the ratio of the four is (0.5-2.5):(1.5-4):(2.5-5.5):(2-4), blowing agent 5%-15%, preferably a combination of formamide, tert-butyl alcohol and isopropanol, the mass ratio of the three is 6:3:2.5, heat-resistant agent is N-phenylmaleimide, the mass ratio is 0.5-3%, and heat stabilizer zinc stearate is 1.5%-3%. Step 6: Weigh the light carbon-coated magnetic metal absorber and the PMI precursor solution in a ratio of 1:1.5% to 1:15% respectively; Step 7: Add the lightweight carbon-coated magnetic metal absorbent to the PMI precursor solution and mechanically stir for 1 h to 5 h; Step 8: The pre-mixed absorbing slurry is uniformly sheared and homogenized again for 1 to 5 times by a shearing and homogenizing device; Step nine: Fill the uniformly dispersed absorbing slurry into a specific mold and polymerize it in a constant temperature water bath at 36°C to 50°C for 10 to 20 days; Step 10: After demolding, the polymerized board is heat treated at 70°C to 90°C for 18 hours and demolded; at 140°C to 220°C, foaming is performed for 6 to 12 hours, and the foamed product is appropriately peeled or trimmed to obtain a lightweight magnetic-carbon composite lossy absorbing PMI foam board.
3. The method for preparing a lightweight magnetic-carbon composite lossy wave-absorbing PMI foam according to claim 2, characterized in that: The heat treatment in step 1 specifically includes: firstly heating from room temperature to 450-600°C at a heating rate of 2-4°C / min, and then maintaining the reaction at a set high temperature of 450-600°C for 2-6 hours.
4. The method for preparing a lightweight magnetic-carbon composite lossy wave-absorbing PMI foam according to claim 2, characterized in that: The high temperature calcination in step three specifically includes: performing programmed temperature calcination in an argon atmosphere, heating to 700-900°C at a heating rate of 5-10°C / min, maintaining the target temperature for 1-4 hours and then stopping the heating to obtain the corresponding light carbon-coated magnetic metal absorbent.
5. The method for preparing a lightweight magnetic-carbon composite lossy wave-absorbing PMI foam according to claim 2, characterized in that: The lightweight carbon-coated magnetic metal absorbent in step 4 includes one or more combinations of carbon-coated iron magnetic absorbent, carbon-coated cobalt magnetic absorbent, and carbon-coated nickel magnetic absorbent.
Citation Information
Patent Citations
Foam wave-absorbing metamaterial and preparation method thereof
CN107586359A
Preparation method of nano-porous carbon coated magnetic nanoparticle compound
CN113708085A
Cited By
Method for preparing light magnetic carbon composite electromagnetic compatibility material by inducing chelate salt through carbon nitride
CN121573672A
Graphene / nickel-cobalt bimetallic oxide / PMI foam composite wave-absorbing material and preparation method and repairing method thereof
CN121628571A